The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1002/net.3230210104
|View full text |Cite
|
Sign up to set email alerts
|

Efficient algorithms for inferring evolutionary trees

Abstract: In this paper, we examine two related problems of inferring the evolutionary history of n objects, either from present characters of the objects or from several partial estimates of their evolutionary history. The first problem is called the Phylogeny problem, and second is the Tree Compatibility problem. Both of these problems are central in algorithmic approaches to the study of evolution and in other problems of historical reconstruction. In this paper, we show that both of these problems can be solved by g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
331
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(332 citation statements)
references
References 12 publications
1
331
0
Order By: Relevance
“…that they can be placed at the leaves of an evolutionary tree within which each site mutates at most once. Haplotype matrices admitting a perfect phylogeny are completely characterised [8] [9] by the absence of the forbidden submatrix…”
Section: Problem: Parsimony Haplotyping (P H)mentioning
confidence: 99%
“…that they can be placed at the leaves of an evolutionary tree within which each site mutates at most once. Haplotype matrices admitting a perfect phylogeny are completely characterised [8] [9] by the absence of the forbidden submatrix…”
Section: Problem: Parsimony Haplotyping (P H)mentioning
confidence: 99%
“…He showed that the BPP problem can be solved in linear time [8]. The problem we consider is an extension called the binary near perfect phylogeny reconstruction (BNPP).…”
Section: Preliminariesmentioning
confidence: 99%
“…Input Assumptions: If no pair of characters in input I contains the fourgamete property, we can use Gusfield's elegant algorithm [8] to reconstruct a perfect phylogeny. We assume that the all zeros taxa is present in the input.…”
Section: Lemma 1 [8] the Most Parsimonious Phylogeny For Input I Is mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous phylogenetic inference methods, e.g. maximum parsimony, maximum likelihood, distance matrix fitting, subtrees consistency, and quartet based methods have been proposed over the years [15,1,14,26,17,27,4]; furthermore, it is rather common to compare the same set of species w.r.t. different biological sequences or different genes, hence obtaining various trees.…”
Section: Introductionmentioning
confidence: 99%